Penggunaan Media Video dan Powerpoint Pada Mata Pelajaran Kimia Materi Larutan Penyangga Dalam Pembelajaran Daring - Ainurridha Musafir; Ardi Kapahang; Jenny Kumajas (Oxygenius Journal Of Chemistry Education, 2021)
The purpose of this research to see is there are differences in student chemistry learning outcomes on buffer solution material on the use of video media with PowerPoint in online learning. The design used in this research is Pretest-Posttest Control Group Design. This research was conducted at SMA N 1 Kotamobagu with class XI MIA A as experimental class 1 (video media) and class XI MIA B (media PowerPoint) as experimental class 2. Normality testing using the Liliefors test showed that the data for both classes were normally distributed, and homogeneity testing using the similarity test of variance showed both classes were homogeneous. Hypothesis testing using two-way Independent Sample T-test with acceptance criteria H0 is -ttable<tcount<+ttable. It is obtained that tcount = -2.09 and ttable = 1.68 which means tcount is in the rejection region of H0, so hypothesis H0 is rejected and H1 is accepted. Therefore, it can be concluded that there are differences in student learning outcomes when using video media using PowerPoint media.